The Effect of Blue Green Algae (Spirulina platensis) Extract in White Rat (RattusNorvegicus) Treated with Excessive Physical Exercise on Leydig Cell Number and Seminiferous Tubules Diameter - Lazuardi, Dimas Yuzrifar Rhavindra; Rimayanti, Rimayanti; Primarizky, Hardany; Sudjarwo, Sri Agus; Utama, Suzanita; Rachmawati, Kadek (KnE Life Sciences, 2017)
The aim of this study was to investigate the effect of Spirulina platensis extract on the amount of Leydig cells, amount of necrotic Leydig cells, and diameter of seminiferous tubules of rats treated with excessive physical exercise. The excessive physical exercise was done through 60 minutes of swimming for 35 days. Twenty white male rats were randomly divided into five groups i.e C-, control group, C+, a group was only receive swimming, T1, T2, and T3 was received 300, 600, and 1200 mg/kg BW of Spirulina platensis and swimming. Spirulina platensis extract was given orally once a day before swimming. ANOVA followed by Duncan analysis showed significant differences among treatments. Excessive physical exercise influenced on male reproduction system through decreasing the amount of Leydig cells. The conclusion was a dose of 1200 mg/kg BW of Spirulina platensis extract could maintain the amount of Leydig cells, protected the Leydig cells from becoming necrotic, and increased the diameter of seminiferous tubules. Keywords: Rattus Norvegicus, Spirulinaplatensis, excessive physical exercise, Leydig cells, seminiferous tubules diameter